PENGARUH TINGKAT KETUAAN DAUN DAN VARIASI SUHU KYURING TERHADAP KOMPOSISI KIMIA DAN PROFIL KOMPONEN RASA UMAMI DAUN SOKAI (Albertisia papuana Becc) - , EVA MAYASARI, S.Pi, Dr. Ir. Supriyadi, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aims of this research were to evaluate the effect of maturity level and , variation curing temperature (27Â°-50Â°C) on chemical composition, umami taste components profile, and consumer acceptance of umami taste onâsokaiâ leaf. The more mature leaf showed decreases in their moisture, ash, protein contents, however, increases in fat and crude fiber content. Either fresh or dried powder of young, mature, and old leaf were containing umami taste components. Young fresh sokai leaf indicated higher Equivalent Umami Concentration (EUC) value than the dried powder form. Curing at temperature of 40Â°C was the best temperature for all maturity level of sokai leaf, it was showed by the highest EUC value. Young leaf, either in fresh or dried powder form showed the highest EUC value were 98716,58 g/100 g and 208,09 g/100 g, respectively. The application of sokai leaf on the luntuh dewen jawaw dish (cassava porridge leaf) at level of 0,3 % was the most preference formula, and the concentration was equivalent to 0,3 % of MSG addition.